Archaeological expedition to al khashbah (2023): Al khashbah KHS-a - Schmidt, Conrad; Maiorano, Maria Pia; Proctor, Lucas (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Several locations north of the village of Al Khashbah have yielded Neolithic remains, most likely due to the area’s accessible chert outcrops and elevated fluvial terrace systems overlooking wadi floodplains. KHS-A, the main Neolithic site in the area, is distinguished by extensive flint scatters, isolated stone constructions, and fireplaces. In 2022, the team excavated a preliminary test trench (KHS-A.1) that yielded a high number of lithics and charcoal samples. Radiocarbon dating placed the age of the complex within the Late Neolithic Period. In 2023, further excavations at KHS-A.13 were undertaken with the goal of confirming the age dating of the site and expanding our understanding of the extent and occupational sequence of the KHS-A complex. The trench consisted of a 3 × 4 m exposure revealing multiple fireplaces, ash pits, and post holes. The investigation of the Neolithic occupations at Al Khashbah seeks to open new routes and further perspectives in the study of Early and Middle Holocene in the broad area between the mountains and the Rub Al Khali desert.
Keywords: Archéologie -- Oman